A Juridical Analysis of the Criminal Prosecution of Public Appraisers in Land Procurement for Public Interest Purposes: A Case Study of Court Decision Number 27/Pid.Sus-TPK/2023/PN.Smr - Tri Setiyo Wicaksono; Dyah Permata Budi Asri; Helvis; I Made Kanthika (GoAcademica Research & Publishing, 2026)
Legal disputes in land acquisition for public interest purposes frequently place public appraisers at risk of criminalization. This vulnerability is driven by two recurring factors: administrative shortcomings within valuation practice and the tendency of disputing parties to direct criminal allegations toward appraisers when they perceive disadvantage in the compensation process. Despite holding a central role in determining valuation opinions, appraisers often operate without a dedicated statutory framework that clearly delineates administrative liability, professional discipline, and criminal responsibility. This study analyzes a land acquisition case from its initial stages through the final adjudication to identify how appraisers become implicated in corruption-related proceedings and to map practical legal risk-mitigation measures. The research examines the applicable land acquisition and anti-corruption legal regimes using a normative juridical (descriptive-normative) method with a statute approach, along with relevant professional standards, to assess the proper construction of actus reus and mens rea in relation to valuation work. The study argues that where alleged misconduct reflects procedural or administrative noncompliance, accountability should prioritize professional and administrative mechanisms, while criminal punishment should be reserved for situations involving demonstrable intent. The findings support stronger legal safeguards for appraisers, including clearer statutory guidance, reinforced professional oversight, and improved documentation and process controls within valuation assignments.